Evidence for specific independence of the shrew (Mammalia: Soricidae) of St. Paul Island (Pribilof Islands, Bering Sea) - Rausch, Robert L; Rausch, Virginia R (Die Gesellschaft, 1997)
(Uploaded by Plazi from the Biodiversity Heritage Library) No abstract provided.